Morpho-functional and biochemical improvements in ram spermatozoa following intraepididymal platelet-rich plasma administration - Cinkara, Serap Dayan; Badilli, Nida; Gungor, Ibrahim Halil; Cihangiroglu, Aslihan Cakir; Acisu, Tutku Can; Ozmen, Gorkem Kirmizikaya; Turk, Gaffari (Elsevier, 2025)
This study evaluated the effects of intraepididymal platelet-rich plasma (PRP) administration on sperm morpho-functional characteristics and biochemical profiles in rams. Twelve healthy one-year-old Akkaraman rams were randomly assigned to control (0.9 % NaCl) and PRP (0.2 mL/per epididymis; similar to 150-200 x10(6) platelets) groups, with six biweekly injections. Semen was collected biweekly and subjected to routine spermatological, flow-cytometric and biochemical assessments. PRP treatment significantly enhanced plasma membrane integrity (P < 0.001), total and rapid motility (P < 0.05), and kinematic parameters including VCL (P < 0.05), VSL, VAP, LIN, and WOB (P < 0.01). Significant reductions were observed in head and total abnormalities (P < 0.001), static spermatozoa (P < 0.05), ALH, and BCF (P < 0.05). Flow-cytometric analyses revealed increased proportions of sperm with high mitochondrial activity (P < 0.01), along with decreased acrosomal damage (P < 0.05) and apoptotic spermatozoa (P < 0.001). Biochemical assays demonstrated a marked reduction in malondialdehyde level (P < 0.001) and increased glutathione level, and glutathione-peroxidase and catalase activities (P < 0.01), indicating improved oxidative status. Although a 10.05 % increase in cholesterol level was observed following PRP administration, the change was not statistically significant. However, PRP significantly elevated margaric (C17:0) and stearic (C18:0) acids (P < 0.05-0.01), vaccenic (C18:1n7) and nervonic (C24:1) acids (P < 0.001), and alpha-linoleic (C18:3n3) and docosapentaenoic (C22:5n3) acids (P < 0.001). These findings suggest that epididymal PRP administration improves sperm quality via enhanced antioxidant capacity, mitochondrial function, and lipid remodeling.
Keywords: Platelet-rich plasma; Epididymis; Ram semen; Oxidative stress; Apoptosis